1998
DOI: 10.4269/ajtmh.1998.58.195
|View full text |Cite
|
Sign up to set email alerts
|

Transmission intensity and Plasmodium falciparum diversity on the northwestern border of Thailand.

Abstract: Genetic analysis of the number of Plasmodium falciparum genotypes per infected person in regions of holoendemic and hyperendemic malaria suggest that in areas of lower transmission intensity, significantly fewer parasite genotypes per infected person should be found. A predominance of single clone infections in the human population could generate the controversial clonal population structure proposed for P. falciparum by Tibayrenc and others. Characterization of P. falciparum from individuals on the Thai-Burme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
64
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 38 publications
(68 reference statements)
11
64
1
1
Order By: Relevance
“…This evidence suggests that more recent selective forces have shaped population structure in this species. Previous studies also suggest that P. falciparum infections in Southeast Asia were more multiclonal two decades ago, again suggesting that recent forces have constrained its genetic diversification (75)(76)(77). This evidence is consistent with our findings that P. falciparum in Cambodia has undergone large demographic shifts much more recently than P. vivax.…”
Section: Discussionsupporting
confidence: 83%
“…This evidence suggests that more recent selective forces have shaped population structure in this species. Previous studies also suggest that P. falciparum infections in Southeast Asia were more multiclonal two decades ago, again suggesting that recent forces have constrained its genetic diversification (75)(76)(77). This evidence is consistent with our findings that P. falciparum in Cambodia has undergone large demographic shifts much more recently than P. vivax.…”
Section: Discussionsupporting
confidence: 83%
“…Genetic variation in areas of hyperendemicity has been found to be greater than that in areas of hypoendemicity (1,18). Previous studies of the genetic variation within the polymorphic region of PvMSP-1 showed several patterns among the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on empirical data indicating that genetic variation is substantial both within and between infections in other Plasmodium species (Babiker & Walliker 1997;Paul et al 1998;Konate et al 1999;Smith et al 1999), we favour a genetic explanation for variation between donor groups. However, we were unable to distinguish between genotype di¡erences between donor infections or di¡erences due to competition between clones.…”
Section: Discussionmentioning
confidence: 99%